2020
DOI: 10.1044/2020_lshss-19-00059
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Sources of Stuttering Disclosure on the Perceptions of a Child Who Stutters

Abstract: Purpose This study measured between-group differences in perceived speech skills and personality characteristics of a 12-year-old boy who stutters as a function of a factual stuttering disclosure statement, delivered by the boy who stutters, his “mother,” or his “teacher.” Method Two hundred seventeen college-aged adults were randomly assigned to one of four groups, including a control group (no stuttering disclosure) and three experimental groups (chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 65 publications
0
12
3
Order By: Relevance
“…Interestingly, mother disclosure eliciting no beneficial shifts in listener perceptions when compared to the control group but rather trended toward a more negative perception of the CWS. Specifically, for select personality characteristic continuum pairs (relaxed/tense, secure/insecure, outgoing/shy), mother disclosure resulted in more negative perceptions of the CWS [18].…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Interestingly, mother disclosure eliciting no beneficial shifts in listener perceptions when compared to the control group but rather trended toward a more negative perception of the CWS. Specifically, for select personality characteristic continuum pairs (relaxed/tense, secure/insecure, outgoing/shy), mother disclosure resulted in more negative perceptions of the CWS [18].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, when PWS achieved a desired level of fluency, listeners typically reported that the speech sounded significantly more unnatural as a result of the therapy [17]. As a result, although traditional therapy might lessen overt stuttering frequency or severity, traditional therapy also appears to be inadequate at eradicating the observative manifestations of the disorder, including the negative consequences of stuttering on the quality of life for those who stutter [1,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations